CLIFF-GRADS workshop summary report - Global Research Alliance on Agricultural Greenhouse Gases; CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The Climate, Food and Farming - Global Research Alliance Development Scholarships (CLIFF-GRADS) is a joint initiative of the CCAFS Low Emissions Development Flagship and the Global Research Alliance on Agricultural Greenhouse Gases (GRA). The CLIFF-GRADS Programme builds capability in early-career PhD scientists from developing countries to conduct applied research in agriculture and food loss and waste emission quantification and mitigation. Since 2011, nearly 100 students have received grants and moved into leadership positions in research institutions and governments all over the world.